Swearing-in Ceremony for New Attorneys Held at Wine Press Room at Selland Arena - Watkins, Howard::::::::: (1989)
Justice Nickolas DiBiaso reading prepared remarks on behalf of the 5th District Court of Appeal, including the duties of an attorney under state law